CHEM ICAL COMPOSITIONS AND PHYTOCHEM ICAL SCREENING OF THE SEEDS OF GARC/NIA KOLA (BITTER KOLA) (Biological Sciences - PJSIR, 2003)
Chemical compositions and pit tochemical screening of the fresh seeds of Garci11ia kola (\\cl \\eight) have been determined The results sho\\cd that the samples contmned lugh moisture content 75 50% while tl1e ash content was folmd to be 5.90°,o. Carbohydrare was 10.85%. crude fat "as 14.50% and crude protein was found  to be  very  low 4.25° o Thc resultsobtained rc\'ealed that the most abundant mineral in the scedsor'Garci11i11 kola issodium (2t 5. 0ppm) The seeds ofGarci11ia  kola also contain  Mg. Cd. 7.n,  K  and  Fe, ho,,cvcr. Mn. Pb. Cu. Cd and  Co \\ere 1101 detected.Prclim1nar phytochemicul sere